2001
DOI: 10.1038/sj.ijo.0801628
|View full text |Cite
|
Sign up to set email alerts
|

Long-term leptin treatment of ob/ob mice improves glucose-induced insulin secretion

Abstract: OBJECTIVE: Previous studies have demonstrated that leptin inhibits glucose-stimulated insulin secretion from isolated islets, although a lack of leptin effect on insulin secretion has also been reported. The effect of long term in vivo leptin treatment of insulin secretion has, however, not been established. Therefore, in the present study, we have evaluated the effect of long term in vivo treatment of leptin on glucose-induced insulin secretion in obaob mice. METHODS: After 7 days' treatment of leptin (100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Whereas sham-treated mice displayed a continuous adaptive growth of islet transplants, this growth was abolished and partially reversed under leptin treatment (Fig. 4 A and B), in agreement with earlier reports (20,21). At the end of the treatment, the proliferation of beta cells was virtually abolished in both the engrafted islets and the in situ pancreatic islets from leptin-treated ob/ob mice (Fig.…”
Section: Leptin Treatment Reduces Body Weight and Corrects Blood Glucosesupporting
confidence: 91%
See 1 more Smart Citation
“…Whereas sham-treated mice displayed a continuous adaptive growth of islet transplants, this growth was abolished and partially reversed under leptin treatment (Fig. 4 A and B), in agreement with earlier reports (20,21). At the end of the treatment, the proliferation of beta cells was virtually abolished in both the engrafted islets and the in situ pancreatic islets from leptin-treated ob/ob mice (Fig.…”
Section: Leptin Treatment Reduces Body Weight and Corrects Blood Glucosesupporting
confidence: 91%
“…4A). This is in accordance with the increased immunostaining for insulin perceived in islets from leptin-treated ob/ob mice (20). The normalization of insulin release in vivo after leptin treatment in the ob/ob mouse has been linked to mechanisms both dependent on and independent of food intake (21).…”
Section: Leptin Treatment Reduces Body Weight and Corrects Blood Glucosesupporting
confidence: 79%
“…It is possible that the intracellular content of triglycerides will determine the effect, 35 and that leptin reduces the triglyceride burden, which at least in a rat model was followed by increased insulin secretion. 36 Consequently, it has been suggested that leptin regulates the metabolism of fatty acids in nonadipose tissue, 37 but owing to dysfunction in leptin signalling, i.e. leptin resistance, this function may not work properly in obesity and reduced b-cells function follows.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin has been demonstrated to inhibit insulin secretion in vitro (15,25,26). However, in vivo studies in diabetic models have shown that leptin treatment improves insulin secretion in ob/ob mice (27), and overexpression of the leptin receptor in a model homozygous for a mutation of the ObRb, the Zucker diabetic rat, restores GLUT2 expression and insulin secretion (28). By using an ObRb-specific antibody, we observed immunoreactivity for this receptor in the ␤-cells of both normal and high-fat islets with no apparent difference.…”
Section: Discussionmentioning
confidence: 99%